Abnormal Properties of Low‐Dimensional Confined Water. Issue 31 (27th June 2021) - Wang, Dianyu; Tian, Ye; Jiang, Lei
Abstract: Water molecules confined to low‐dimensional spaces exhibit unusual properties compared to bulk water. For example, the alternating hydrophilic and hydrophobic nanodomains on flat silicon wafer can induce the abnormal spreading of water (contact angles near 0°) which is caused by the 2D capillary effect. Hence, exploring the physicochemical properties of confined water from the nanoscale is of great value for understanding the challenges in material science and promoting the applications of nanomaterials in the fields of mass transport, nanofluidic designing, and fuel cell. The knowledge framework of confined water can also help to better understand the complex functions of the hydration layer of biomolecules, and even trace the origin of life. In this review, the physical properties, abnormal behaviors, and functions of the confined water are mainly summarized through several common low‐dimensional water formats in the fields of solid/air–water interface, nanochannel confinement, and biological hydration layer. These researches indicate that the unusual behaviors of the confined water depend strongly on the confinement size and the interaction between the molecules and confining surface. These diverse properties of confined water open a new door to materials science and may play an important role in the future development of biology. Abstract : Physical properties of low‐dimensional confined water are summarized through several common forms ranging from artificial to biological areas. The confinement size and surface properties affect the water behavior and destroy the tetrahedral hydrogen bond coordination mode which results in its intrinsic properties changing seriously. Reviewing confined water can help understand some abnormal biological phenomena, and guide the artificial designs.